Histórias de vida e trabalho: potências e desafios da rede substitutiva de saúde mental de São João da Boa Vista/SP - Theodoro, Camila Roman [UNIFESP] (2014)
This research consists of a qualitative study about the organization of life and work, their forms of insecurity, and inequality of classes, with emphasis on individuals with serious mental disorders, which are often on the margins of a possible inclusion in work activities with the overall objective to analyze the history of life and work, as well as the potential and challenges of users in a Psychosocial Care Center (CAPS), and specific objectives to meet municipal social assistance network and its available resources; investigate the possible interests of social inclusion through labor; ascertain the challenges encountered from the possibilities of this approach; and recognize the potential of each participant search user. Methodologically, the data collection was performed by privately observing each participant, the documentary analysis of records of service users and semi-structured interviews, from which were produced individualized narratives, fitting highlight to the 236 (two hundred and thirty six) members attended the CAPS II, fourteen (14) participated in the study on screen. From the analysis and discussion of the data was the finding that labor makes possible the reintegration of man with psychic disorders in society, which sees him new meanings for life.